DAILY LIFE OF YOUTH AND THE VIRTUAL WORLD - Toychiyev Anvar Nabijonovich (European Journal of Humanities and Educational Advancements, 2023)
The relevance of social problems among youth in the information society is explained by the human search for spiritual guidance and stability in the world of endless telecommunication simulations. Under the influence of the information revolution of young people, elements of traditional culture are being modernized, gradually entering the Internet around the world, showing significant adaptability to technological innovations. In this article, the importance of virtual space in the life of young people, new trends in the description of virtualization in sociological research, a comparative analysis of modern youth social relations is made